The aptamer BT200 effectively inhibits von Willebrand factor (VWF) dependent platelet function after stimulated VWF release by desmopressin or endotoxin - Kovacevic, Katarina D. (Sci Rep, 2020)
Von Willebrand factor (VWF) plays a major role in arterial thrombosis. Antiplatelet drugs induce only a moderate relative risk reduction after atherothrombosis, and their inhibitory effects are compromised under high shear rates when VWF levels are increased. Therefore, we investigated the ex vivo effects of a third-generation anti-VWF aptamer (BT200) before/after stimulated VWF release. We studied the concentration-effect curves BT200 had on VWF activity, platelet plug formation under high shear rates (PFA), and ristocetin-induced platelet aggregation (Multiplate) before and after desmopressin or endotoxin infusions in healthy volunteers. VWF levels increased > 2.5-fold after desmopressin or endotoxin infusion (p < 0.001) and both agents elevated circulating VWF activity. At baseline, 0.51 µg/ml BT200 reduced VWF activity to 20% of normal, but 2.5-fold higher BT200 levels were required after desmopressin administration (p < 0.001). Similarly, twofold higher BT200 concentrations were needed after endotoxin infusion compared to baseline (p < 0.011). BT200 levels of 0.49 µg/ml prolonged collagen-ADP closure times to > 300 s at baseline, whereas 1.35 µg/ml BT200 were needed 2 h after desmopressin infusion. Similarly, twofold higher BT200 concentrations were necessary to inhibit ristocetin induced aggregation after desmopressin infusion compared to baseline (p < 0.001). Both stimuli elevated plasma VWF levels in a manner representative of thrombotic or pro-inflammatory conditions such as arterial thrombosis. Even under these conditions, BT200 potently inhibited VWF activity and VWF-dependent platelet function, but higher BT200 concentrations were required for comparable effects relative to the unstimulated state.